Chronological age of Alpine ski medal winners in the 2015-2018 Olympic cycle - Savic, Z.; Stojanovic, N.; Tomic, M.; Savic, D. (SportLogia, 2021)
Personal motivation, as well as engagement in alpine skiing, brought the authors to inspect the differences in average chronological age of alpine skiers, and to present the results to the professional public, in order to improve planning and programming of the training process. The paper analyzed the average chronological age of medal winning professional alpine skiers in the World Cups in the 2015-2018 Olympic cycle. The following alpine disciplines were analyzed: Slalom (SL), Giant Slalom (GS), Super-G (SG), Downhill (DH) and Alpine Combination (AC). The obtained results indicate that there was a significant difference in the average chronological age between male and female competitors. The results of the present study show that there were differences in GS, SG, DH, and AC, where male skiers are on average older than female skiers. Conversely, there was no significant difference between male and female skiers in SL. The results of this study could aid coaches and experts in future years of individual management of sports careers of male and female skiers.